A comparative evaluation of the efficacy of manual, magnetostrictive and piezoelectric ultrasonic instruments: an in vitro profilometric and SEM study - Sumita Singh; Ashita Uppoor; Dilip Nayak (University of São Paulo, 2012)
OBJECTIVES: The debridement of diseased root surface is usually performed by mechanical scaling and root planing using manual and power driven instruments. Many new designs in ultrasonic powered scaling tips have been developed. However, their effectiveness as compared to manual curettes has always been debatable. Thus, the objective of this in vitro study was to comparatively evaluate the efficacy of manual, magnetostrictive and piezoelectric ultrasonic instrumentation on periodontally involved extracted teeth using profilometer and scanning electron microscope (SEM). MATERIAL AND METHODS: 30 periodontally involved extracted human teeth were divided into 3 groups. The teeth were instrumented with hand and ultrasonic instruments resembling clinical application. In Group A all teeth were scaled with a new universal hand curette (Hu Friedy Gracey After Five Vision curette; Hu Friedy, Chicago, USA). In Group B CavitronTM FSI - SLI TM ultrasonic device with focused spray slimline inserts (Dentsply International Inc., York, PA, USA) were used. In Group C teeth were scaled with an EMS piezoelectric ultrasonic device with prototype modified PS inserts. The surfaces were analyzed by a Precision profilometer to measure the surface roughness (Ra value in µm) consecutively before and after the instrumentation. The samples were examined under SEM at magnifications ranging from 17x to 300x and 600x. RESULTS: The mean Ra values (µm) before and after instrumentation in all the three groups A, B and C were tabulated. After statistically analyzing the data, no significant difference was observed in the three experimental groups. Though there was a decrease in the percentage reduction of Ra values consecutively from group A to C. CONCLUSION: Within the limits of the present study, given that the manual, magnetostrictive and piezoelectric ultrasonic instruments produce the same surface roughness, it can be concluded that their efficacy for creating a biologically compatible surface of periodontally diseased teeth is similar.